A Functional Near Infrared Spectroscopy Investigation of the Physiological Underpinnings of Visual Cognitive Workload After Concussion. Issue 5 (31st May 2022) - Master, Christina; Storey, Eileen; Wang, Lei; Grady, Matthew; McDonald, Catherine; Margulies, Susan; Arbogast, Kristy; Ayaz, Hasan
Background: In concussion, functional near infrared spectroscopy (fNIRS) has been shown to detect differences in cortical oxygenation during neurocognitive testing, with concussed adults manifesting less task-based cortical activation compared to controls. In addition, fNIRS has identified significantly reduced interhemispheric coherence in adult concussions relative to controls. In addition, adults with greater post-concussive symptom burden demonstrate lower task-related oxygenation in the frontal and dorsolateral prefrontal cortex (DLPFC) and reduced connectivity compared to controls. Hypothesis: The goal of this study was to use fNIRS to identify any differences in visual task-related cortical activation between concussed adolescents and healthy controls while performing a the King-Devick (KD) test. Methods: We enrolled 112 adolescents, ages 12-18 years, with recent concussion and 165 healthy controls as part of a large observational prospective cohort. Participants were provided standardized instructions to read the KD cards while wearing the fNIRS sensor pad. The relative changes in the difference of oxy-and deoxy-hemoglobin concentrations over each task condition for each optode were calculated via the Modified Beer-Lambert Law using local baselines for each task condition period as its beginning. The averaged oxy-hemoglobin concentration changes for each task period were used for statistical analysis of group (e.g., concussed vs healthy) effect. Results: The concussed adolescents (n=112) and healthy controls (n=165) were demographically comparable with respect to age, sex, and race/ethnicity. The concussed group was more likely to have a history of prior concussion (p = <.0001) and migraine (p = .0001) compared to the healthy control group (Table 1). The concussed adolescents were assessed with fNIRS while performing a visual task a median of 10 days after injury (IQR 4-16). The concussed group had significantly lower oxygenation changes that are the difference between oxygenated and deoxygenated hemoglobin as an indicator of task-evoked response, on left lateral prefrontal area (p<.005, FDR q<.005). As expected, there was also a main effect for task condition (cards) at right lateral prefrontal cortex (p<.001, FDR q<.005). Conclusions: fNIRS is able to distinguish concussed adolescents from healthy controls while performing a visual-cognitive task, the K-D test. Injured adolescents with concussion demonstrated a compensatory pattern of cortical activation, suggesting localized brain dysfunction, recruiting from both hemispheres, distinguishing it from the pattern of cortical activation in healthy controls. fNIRS, as a modality, is not only able to differentiate concussion from healthy controls, but also captures the compensatory mechanisms of cortical activation that underlie visual cognitive function after injury.